Book Review: Entrepreneurship and Management in an Islamic Context - Puspita, Amalia Tri (SMART Insight, 2024)
The book Entrepreneurship and Management in an Islamic Context examines the relationship between Islamic values and modern entrepreneurship and management practices. Edited by Veland Ramadani, Lé́o-Paul Dana, Shqipe Gërguri-Rashiti, and Vanessa Ratten, this work brings together various multidisciplinary perspectives on how Islamic teachings, culture, and ethics shape entrepreneurial behavior, leadership, and innovation in a global context. This article summarizes and analyzes the main ideas of the book, highlighting the role of religion in shaping business behavior, the Islamic leadership model, social entrepreneurship, and the empowerment of Muslim women and youth. Entrepreneurship and management from an Islamic perspective offer an alternative paradigm to the conventional profit-oriented capitalist system. This approach brings moral and spiritual dimensions back into business practice, so that the economy is no longer a tool of exploitation, but a means to achieve al-falah.